Observing mother-child interaction in a free-play vs. a structured task context and its relationship with preterm and term born toddlers' psychosocial outcomes - Krijnen, L. J. G; Verhoeven, M.; van Baar, A. L. (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction High quality of mother-child interaction is associated with better psychosocial outcomes in children. However, this association might depend on the context in which mother-child interaction is observed as well as specific child characteristics. In this study, we examine differences in the assessment of mother-child interaction in a free-play and a structured task context. In addition, it will be investigated whether the behaviors per context are differently associated with preterm vs. term born toddlers' psychosocial outcomes. Methods A total of 201 Dutch mother-child dyads participated in the study, of whom 108 children were moderate to late preterm (MLP) and 93 were born at term. Mother-child interaction was observed in a free-play and a structured task context when the child was 18 months of (corrected) age. Six subscales of mother-child interaction were assessed using the Coding Interactive Behavior scheme: maternal stimulation, maternal warmth, child's negative affect, active mother and child engagement, dyadic synchrony and tense interaction. Psychosocial outcomes were assessed at 24 months of (corrected) age using the Ages and Stages Questionnaire – Social Emotional and the Child Behavior Checklist. Results Mother-child interaction was reliably assessed (α > .60) in each context, except for tense interaction during free-play (α = .41) and child's negative affect when averaged across contexts (α = 0.55). Compared to the free-play context, during the structured task, more child's negative affect, tense interaction and active mother and child engagement was observed in MLP and term born children, and less dyadic synchrony in MLP children (p's < .01). Only during a structured task and for term born children, active mother and child engagement was related to less social-emotional difficulties, internalizing and externalizing behaviors. Only during free-play and for MLP children, active mother and child engagement was related to less externalizing behaviors. Dyadic synchrony during a structured task was associated with less social-emotional difficulties in MLP and term born children, and dyadic synchrony during free-play was only associated with less social-emotional difficulties in term born children (all p's < .05). Discussion Most mother-child interactive behaviors can be reliably assessed in both contexts. The structured task context elicited more varied behaviors than the free-play context. With the observations in the structured task context, more associations with children's psychosocial outcomes were found than with the observations in the free-play context. Mother-child interactions characterized by active, engaged and synchronous behaviors were associated with better psychosocial outcomes in toddlers, with some differences observed for MLP vs. term born children and for the free-play vs. the structured task context. Suggestions for future research as well as clinical practice are provided.